Which criteria are important in usability evaluation of mHealth applications: an umbrella review - Zahra Galavi; Mahdieh Montazeri; Reza Khajouei (BMC Medical Informatics and Decision Making)
Abstract Introduction Usability plays a critical role in the design of mHealth applications. A well-designed app enhances user experience and contributes to better healthcare outcomes. However, it remains unclear which usability criteria are often neglected, leading to issues in the actual use of these applications. This study aimed to identify and categorize the usability issues of mHealth applications, mapping them to Nielsen’s usability principles to determine the most critical criteria. Methods The PRISMA guidelines were followed to report the results. Different databases (PubMed, Scopus, WoS) were searched for systematic reviews and/or meta-analyses about usability evaluation in mHealth applications. Two reviewers independently applied predefined selection criteria, extracted data, and assessed methodological quality using the AMSTAR tool. Results Eight studies met the inclusion criteria. The most common method used in studies to evaluate the usability of mHealth applications was the questionnaire. Researchers identified 79 usability issues from the studies. Eleven of the issues were related to the Aesthetic and minimalist design category. The category of Flexibility and efficiency of use was next (n = 10). Conclusion This study identified the usability issues that individuals face when using mHealth applications. By mapping these issues to evaluation criteria, developers can systematically address and prevent them. Attention to these issues will lead to better design and more effective use of mHealth applications.